Social thermoregulation in the subterranean Mashona mole-rat (Fukomys darlingi): the role of socio-physiological effect - Wiedenová, Pavlína (Jihočeská univerzita, 2014)
Life underground is one of the most challenging tasks for animals. The subterranean environment is seasonally and diurnally stable and provides shelter from predators. On the other hand food is scarce, the cost of digging is very high and closed burrows create hypoxic and hypercapnic conditions. Thus the physiological and behavioral adaptations to save energy are very important for underground dwellers. Social thermoregulation is such behavioral adaptation. Additionally, it has been suggested that social animals suffer from ?isolation stress? and that they decrease their metabolic rates when other family members are present = socio-physiological effect. In this study I measured the resting metabolic rates (RMR) of social Mashona mole-rats (Fukomys darlingi) in isolated individuals, pairs and groups of three to eight individuals. Measurements were carried out at two ambient temperatures, in the thermoneutral zone (TNZ; 30°C) to test the presence of a socio-physiological effect and below their TNZ (20°C) to test the effect of social thermoregulation. A socio-physiological effect was distinctive neither in pairs nor in larger groups. At temperature below the TNZ the Mashona mole-rat saved 21% of its energetic expense in pairs due to social thermoregulation. With an increase in group size, energetic savings rose up to four animals. In larger groups, social thermoregulation did not influence the energetic expenditure, possibly because Mashona mole-rat´s families naturally contain around four to five adults.
Social thermoregulation in the subterranean Mashona mole-rat (Fukomys darlingi): the role of socio-physiological effect
Keywords: Mashona mole-rat; socio-physiological effect; social thermoregulation; RMR